Mewujudkan Karakter Digital Mahasiswa Hukum dalam Era Society 5.0 dengan E-Court melalui Magang Profesi Kantor Advokat Dyah Setyanwati, S.H & Associates Merdeka Belajar Kampus Merdeka - Antonius Ivananda Dias Wijaya; Chintya Audrey Margaretha Silaen; Ivana Gracia Putri; Mochammad Awaludin Rizqi Nurhasan; Putri Nanda Sari Sirait (CV. Ulil Albab Corp, 2022)
The rapid development of the times, especially the development of technology and information in the era of the industrial revolution 4.0 resulted in the birth of society 5.0 which makes technology part of the human being himself. In law enforcement in Indonesia, it is necessary to innovate the use of technology in proceedings so as to give birth to those that support e-court as a solution to some of the problems that exist in the judiciary in Indonesia. This study aims to analyze how the mechanism of proceeding with e-court (electronics justice system) is used in resolving cases in court and how e-court is implemented in court in accordance with the principle of simple, fast and low-cost justice. To achieve these objectives, this study uses normative juridical research methods using statutory approaches (statute approach), conceptual approaches, analytical approaches (analytical approach), and theoretical approaches (theoretical approach).